Automated Pet Feeder Called Smart Pakan using 3D Printer with Open Source Control System - Rizaldy Hakim Ash Shiddieqy; Bayu Adhi Saputro; Fatan Odhi Dandha; Liza Rusdiyana (Institut Teknologi Sepuluh Nopember, 2020)
In this paper, an automatic pet feeding machine is built using the 3D Printer machine and an opened source control system to help people with busy activities to be able to feed their pets on time. The machine is built using 3D Printer machine. The control system is built using the NodeMCU ESP8266 platform module and ultrasonic sensors. The controlling device uses a smartphone that is installed blynk application software that has the principle of the Internet of Things. The machine works by opening it’s valve to control the water’s discharge, a servo motor to open the feed container, as well as a timer to regulate the time of feeding. The valve can be set in 4 conditions. There are 10 degrees, 20 degrees, 30 degrees and up to 40 degrees. Then for the feed distance’s display it will provide information about the distance of the feed to the sensor, for a maximum distance of 9 cm in accordance with the distance sensor attached to the roof of the feed container with the sensor attached to the bottom of it. This machine can work continuously and automatically as long as there is an electricity source in the house and the owner holds the control of the blynk application software on their phone.